(untitled) (As-Sahla: Journal Of Islamic Studies, 2025)
This study examines women’s leadership from the perspective of hadith, an issue that continues to generate debate among scholars and Muslim communities. The background of this research lies in the differing interpretations of the hadith narrated by Abu Bakrah which states, “A people who entrust their affairs to a woman will never prosper.” The objective of this study is to analyze the validity of the hadith’s sanad and matn as well as to explore its relevance to contemporary leadership. This research employs a qualitative method using library research, by applying sanad criticism, matn criticism, and contextual-historical approaches integrated with the framework of maqāṣid al-sharī‘ah. The findings indicate a sharp distinction between classical scholars who understood the hadith textually as a universal prohibition, and contemporary scholars who interpret it as a situational response to the political turmoil in Persia. This analysis identifies a common ground that leadership in Islam is determined by capacity, trustworthiness, and justice rather than gender. The novelty of this study lies in synthesizing hadith criticism with contemporary social analysis, offering a reinterpretation that is more relevant to current gender equality discourse. The implication is the need for a contextual understanding of hadith to address the challenges of women’s leadership in modern society.